IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI PONOROGO NOMOR 60 TAHUN 2020 TENTANG PERCEPATAN PENANGGULANGAN KEMISKINAN BERBASIS DATA TERPADU KESEJAHTERAAN SOSIAL (DTKS) DI KECAMATAN NGEBEL KABUPATEN PONOROGO PROPINSI JAWA TIMUR - Tiena Sulistyarini (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The research aims to describe the extent to which the implementation of thePonorogo Regent Regulation Policy Number 60 of 2020 concerning theAcceleration of Poverty Reduction Based on Integrated Social Welfare Data inPonorogo Regency, East Java Province provides complete up to date andintegrated poverty data information that will be used by the government in order toprovide poverty management programs. particularly in the Non Cash GovernmentAssistance (BPNT) Staple Food program for the community. BPNT-Staple Food isassistance provided by the Government for poverty alleviation and the welfare ofBeneficiary Families. The background of the problem in this study is based onpreliminary observations that many people do not understand the mechanism of thedata collection process until the distribution results in the community notappreciating the government's commitment to poverty reduction.Keywords: Government Assistance Programs, Implementation, Poverty Data